Kepastian Hukum dan Kekuatan Pembuktian Sertipikat Tanah Elektronik - Siregar, Tania Tri Dewi; Sudarti, Elly; Bakar, Firdaus Abu (Wajah Hukum, 2024)
The purpose of this research is to analyze the legal certainty and evidentiary strength of electronic certificates against land rights holders as a valid proof of ownership, which is generally in physical form. Based on the UUPA and PP 24/1997, land certificates in the form of documents hold the position of written evidence. However, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has issued a policy regarding electronic certificates regulated in the Ministerial Regulation of Agrarian Affairs and Spatial Planning/National Land Agency Number 1 of 2021 concerning Electronic Certificates. The research method used is normative juridical with an approach through legislation. The research results indicate that the conversion of land certificates from physical to electronic form can only be carried out on land that has already been registered through a data maintenance application submitted by the rights holder. The legal certainty depends on whether or not a request for data maintenance has been submitted. In terms of proof, electronic certificates provide protection to the rights holder as an electronic evidence tool, which is demonstrated in two ways: by showing it directly from the electronic system and also by presenting the printed result.